2021
DOI: 10.1111/1756-185x.14097
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Growth Differentiation Factor 5 rs143383 and asporin D‐repeat polymorphisms in patients with hand and knee osteoarthritis in Kurdistan province, Iran

Abstract: Osteoarthritis (OA) is a degenerative joint disease, which occurs when the cartilage or cushion between the joints breaks down, leading to pain, stiffness, and swelling. OA is characterized by the degeneration of articular cartilage. 1 Several factors lead to the development of OA, including excess weight, injury, aging, and hormonal, environmental, and genetic factors, which are recognized as major risk factors for OA. 2 This disease occurs when mechanical stress and inflammatory mediators cause an imbalance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…All eighteen studies [ 10 27 ] presented the OA of knee, hip and hand data. In the studies of the correlation between the GDF5 rs143383 SNP and OA of knee, hip and hand, the meta-analysis showed that GDF5 rs143383 SNP codominant heterozygote model (OR = 1.17, 95% CI 1.07–1.27) is associated with the susceptibility to OA of knee, hip and hand.…”
Section: Resultsmentioning
confidence: 99%
“…All eighteen studies [ 10 27 ] presented the OA of knee, hip and hand data. In the studies of the correlation between the GDF5 rs143383 SNP and OA of knee, hip and hand, the meta-analysis showed that GDF5 rs143383 SNP codominant heterozygote model (OR = 1.17, 95% CI 1.07–1.27) is associated with the susceptibility to OA of knee, hip and hand.…”
Section: Resultsmentioning
confidence: 99%
“…40 Currently, the primary goal of OA treatment is to reduce OA patients' complaints of joint pain, swelling, and dysfunction. 41,42 Other OA medications and NSAIDs are only momentarily beneficial, and excessive use might have negative side effects. 43 Therefore, it is necessary to discover safe and effective strategies to alleviate the clinical symptoms of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Генетические факторы играют важную роль в развитии и прогрессировании ОА [7]. Ряд исследований указывают на различия в ассоциациях отдельных полиморфных генетических маркеров с ОА коленного сустава у мужчин и женщин [8][9][10]. В результате полногеномных исследований (GWAS) выявлено более 120 однонуклеотидных полиморфизмов (SNP), ассоциированных с развитием ОА различных локализаций (p ≤ 5 × 10 Примечание: результаты получены методом MB-MDR с учетом коррекции на ковариаты, NH -количество значимых сочетаний генотипов, ассоциированных с повышенным риском развития ОА коленного сустава, beta H -коэффициенты логистической регрессии для рисковых сочетаний генотипов, WH -статистики Вальда для рисковых сочетаний генотипов, NL -число значимых сочетаний генотипов, ассоциированных с низким риском развития заболевания, beta L -коэффициенты логистической регрессии для протективных сочетаний генотипов, WL -статистики Вальда для протективных сочетаний генотипов, p perm -уровень значимости моделей после проведенного пермутационного теста (выполнено 1000 пермутаций) с учетом коррекции на ковариаты.…”
Section: остеоартрозunclassified